Evidence of effectiveness of clinical audit in improving histopathology reporting standards of mastectomy specimens. Issue 1 (January 1998) - Appleton, M A; Douglas-Jones, A G; Morgan, J M
Abstract : AIM: To assess the effectiveness of clinical audit in improving standards in histopathological reporting of mastectomy specimens. METHODS: Reports on mastectomy specimens containing tumour issued by non-specialist histopathologists in 1990, 1992, 1994, and 1996 were scored for their information content. There were 10 reports evaluated from each year. Before 1990 no reporting guidelines had been formulated within the department. The audits in 1992 and 1994 were performed after agreed written guidelines (including the establishment of six essential pieces of information), and in 1996 the specimens were reported using a proforma. RESULTS: There was a significant increase in information after the introduction of written guidelines but there was a reduction in information over time. In 1990 none of the 10 reports included all six pieces of mandatory information; in 1992 four of the reports contained all mandatory information; in 1994 only one report contained all mandatory information. The introduction of a proforma for reporting resulted in further significant improvement with all 10 reports in 1996 containing all mandatory information. CONCLUSIONS: Successive rounds of audit increases the standard of reporting in histopathology. There is a need for continuing monitoring of standards as these may deteriorate over time. Reporting complex specimens on a proforma has a significant beneficial effect on information content.